Occupational Exposures to Blood and Body Fluids (BBFS) among Health Care Workers and Medical Students in University of Gondar Hospital, Northwest of Ethiopia (Global Journal of Medical Research, 2013)
Introduction: Occupational exposure to blood and body fluid is a serious concern for health care workers. The problem is more devastating in developing countries like Ethiopia with poor infrastructure and health setup. This study tried to assess the magnitudes of occupational exposure and its associated factors among HCWs and medical students to BBFs in University of Gondar Hospital. Methods: A cross sectional survey was conducted from September 6 to October 2, 2012, in University of Gondar hospital. Two hundred eighty five participants (including health professionals, janitors and medical students) were participated in the study. Stratified simple random sampling technique was used to select the participants. Data was collected through Self-administered questionnaire and interview using structured questionnaire. Result: The overall lifetime and one year prevalence’s of occupational exposure to BBF during the study period were 177(70.2%) and158 (62.9%), respectively. The exposure rate of BBFs in the last-one year was highest among interns 29(90.6%), followed by health professionals 100(63.3%) and least among housekeeping staffs 28(45.2%).
Keywords: occupational exposure; health care workers; blood and body fluid